A violência na colônia: os crimes de sacrilégio no Bispado de São Paulo - 1745-1800 - Barroso, Walter Mesquita (2021)
The object of this research are the crimes of sacrilege by blood effusion, committed in the Bishopric of São Paulo, in the second half of the 18th century. religiosity: Why, despite the rigid control that the Church tried to exert over the faithful, were there those who committed crimes in the sacred space? The methodology consists of the analysis of 27 pieces of Ecclesiastical Justice, including investigations, releases, requests for release and clemency, in which the voices of witnesses, victims, lawyers and defendants can give details about the daily life of the 18th century in the Captaincy of São Paulo. The Church tried to sacralize society, but society responded in different ways. The First Constitutions of the Archbishopric of Bahia have an obligatory presence at the heart of this work, as they are considered, by many Brazilian historians, as the first Catholic code to apply to the entire Colony and, from them, spread to Portuguese America , the ideas of the Council of Trent which was Rome's reaction to the Lutheran Reformation. The choice for the theme was due to the few existing researches on the specific theme. Other types of crime, such as those of the flesh and heresies, which were targeted by the Court of the Holy Office, receive more attention from historiography. The crimes of bloodshed are notable when there was clashes, injuries and even death within the Church or in her churchyard